The Role of Driving Teachers in Implementing the Independent Curriculum at SMA Negeri 1 Sakra - Majdi, Muhamad; Mustari, Mohamad; Kurniawansyah, Edy; Alqadri, Bagdawansyah (Mataram University, 2024)
Education is the main pillar in determining the quality of human resources and the progress of a nation, and independent learning is a response to the needs of the education system in an effort to improve human resources in the era of the industrial revolution 4.0. Freedom of learning also frees educators and students to choose their learning system. The qualitative approach is the collection of data in a natural setting with the intention of interpreting the phenomena that occur, where the researcher is the key instrument, the data collection technique is carried out in a triangulation (combined) manner, the analysis is inductive/qualitative, and the results of qualitative research emphasize meaning and generalization. The researcher found that some of the supporting factors for driving teachers in implementing the independent curriculum that already have the status of driving schools and independent independent are the ones that are the driving schools. The supporting factors experienced by the driving teachers in implementing the independent curriculum at SMA Negeri 1 Sakra which develop competence, full support, and inhibiting factors. The impact given as a driving teacher who provides learning that is in accordance with interests, talents, and student-centered. In addition, driving teachers must prioritize caring for the character of students who are increasingly visible, and can also open their minds to students who have different characteristics.